In-Plane Strengthening of Unreinforced Masonry Walls by Glass Fiber-Reinforced Polyurea - Seung-Hwan Son; Jae-Hyoung An; Jun-Hyeok Song; Yu-Sik Hong; Hye-Sook Jang; Hee-Chang Eun (Civil Engineering Journal, 2021)
Strengthening techniques have been employed in Korea to unreinforced masonry walls (UMWs) for several years to protect them from damage caused by the intermittent occurrence of earthquakes. Polyurea, which has a high tensile strength and elongation rate, can be utilized as a strengthening material to enhance the in-plane strength and ductility of UMWs. Glass fiber-reinforced polyurea (GFRPU) is a composite elastomer manufactured by progressively adding milled glass fiber to polyurea. The purpose of this study is to investigate the enhancement of the in-plane strength and ductility of UMWs using GFRPU, depending on the shape of the GFRPU coating on the wall. Four masonry wall specimens are tested with test variables of the number of strengthening sides and coating shapes. It is illustrated that the GFRPU reinforcement of masonry wall leads to enhanced load-carrying capacity, ductility, and energy absorption. An empirical formula to represent the degree of strengthening effected by GFRPU is proposed in this study. Doi: 10.28991/cej-2021-03091782 Full Text: PDF